Australian early childhood educators and infant feeding: a qualitative analysis using social cognitive theory. Issue 5 (4th April 2021) - McGuire, Julianne; Irvine, Susan; Smith, Julie; Gallegos, Danielle
ABSTRACT: Early Childhood Education and Care (ECEC) services are vital in the establishment of optimal infant and young child feeding (IYCF) practices and long-term health. This qualitative study, informed by Social Cognitive Theory, aimed to describe ECEC infant feeding environments. Nineteen formal long day care and family day care ECEC services and 124 educators in metropolitan and regional Queensland, Australia participated in interviews and professional conversations. Inductive and deductive analysis identified three key themes: 'agency', 'IYCF environment', and 'monitoring/surveillance'. This research has identified the key environmental, behavioural and cognitive factors that contribute to optimal IYCF practices in Australian ECEC. Tensions and negotiation between educators, parents, infants and the regulatory framework operate to develop collective agency. Key recommendations are: increasing the visibility of infants in ECEC policy frameworks and building educator and parent self-efficacy in supporting infant agency in order to meet shared goals related to optimal infant health and well-being.